Miejsce świadectwa w przepowiadaniu homilijnym - Dyk, Stanisław (Verbum Vitae, 2015)
The homily is a natural place to give Christian witness. God’s self-revelation – the continuation of which is found in the preaching of God’s Word – is characterized by dialogue. God, in giving Himself through the preaching of the Word, witnesses about Himself and waits for man’s reply, which is born from man’s personal experience of meeting God. This response then takes on the character of man’s own witness about meeting God. The witness of a Christian’s life is the confirmation of the power of God’s Word, it’s verification and illustration. When preaching a homily, witnessing to the faith can be voiced in different ways, but is always to be proclaimed by the homilist. The preacher of God’s Word can indirectly deliver experiencing God through one of the believers, or in his own words. The homilist is to witness that he "saw and heard" (experienced) God – in the Word of God, in the liturgy, and the lives of believers. Thus, the homily is listening to Christ who is present in Sacred Scripture, perceiving Him in the framework of the liturgy, and giving witness about His work in the life of the believer.